1997
DOI: 10.1111/j.1525-1594.1997.tb03720.x
|View full text |Cite
|
Sign up to set email alerts
|

Realization of a Permanent Implantable Pulsatile Impeller Heart with Magnetically Suspended Motor

Abstract: A permanent impeller heart that could work for years was once an idea. However, now this idea is turning into reality through the use of the magnetically suspended motor. Recently, with our implantable pulsatile impeller pump, 3 left ventricular assisted calves survived for about 2 months (62, 54, and 46 days, respectively). The termination of the experiments was related to wear of the mechanical bearing, which resulted in vibration of the rotor and pump failure. All the experimental animals were in good condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2001
2001
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The square‐waveform can be synchronized with an electrocardiogram to produce diastolic augmentation and counterpulsation, which will increase the coronary blood flow. The impeller centrifugal VAD meets most requirements for an artificial heart (4,8). It can produce a physiological pulsatile blood flow with computer signal processing synchronized with heart beats without damaging blood elements or organ function, it can work in nonpulsatile blood flow according to necessity, it is totally implantable and functions as a VAD or total heart, and it costs much less than the diaphragm heart.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The square‐waveform can be synchronized with an electrocardiogram to produce diastolic augmentation and counterpulsation, which will increase the coronary blood flow. The impeller centrifugal VAD meets most requirements for an artificial heart (4,8). It can produce a physiological pulsatile blood flow with computer signal processing synchronized with heart beats without damaging blood elements or organ function, it can work in nonpulsatile blood flow according to necessity, it is totally implantable and functions as a VAD or total heart, and it costs much less than the diaphragm heart.…”
Section: Discussionmentioning
confidence: 99%
“…1). The pulsatile flow can be achieved by changing the rotating speed via introduction of a square‐waveform voltage into the motor coil (8). This construction showed that the T‐VAD has competent pulsatile flow.…”
mentioning
confidence: 94%
“…The animal experiments demonstrated the blood compatibility and ow pulsatility of the device, but the brush DC motor limited its durability and implantability. Efforts had been put to develop a maglev impeller TAH since then [7,8], it resulted in some new problems, such as complicated construction and control, considerable additional consumption of energy and lower reliability, etc.…”
Section: Introductionmentioning
confidence: 99%